Alrerations of gluathione S - transferase and matrix metalloproteinase - 9 expression in gastroesopageal reflux disease and esophageal carcinoma - Ehab Hamed Elsayed; Magda Mourad; Naglaa Ali Zayed; Sameh Labib (Cairo : Ehab Hamed Elsayed, 2012)
The earlier diagnosis of adenocarcinoma is associated with higher cure rate . Identification of biomarkers might provide a better understanding of the process of malignant transformation and helps to identify early markers of malignant transformation in Barrett's esophagus , a known pre - malignant lesion .
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Tropical Medicine
Issued also as CD
Keywords: Barrett's metaplasia; Gluathione S - transferase; Matrix metalloproteinase - 9